Coordinated control strategy for vehicle‐to‐grid support at distribution node. Issue 2 (22nd November 2022) - Thirugnanam, Kannan; Yuen, Chau; Kumar, Praveen; Ghaoud, Tareg; Sgouridis, Sgouris
Abstract: The increasing number of electric vehicles (EVs) creates voltage rise/drop problems when integrated into a distribution node (DN). This generally occurs when EVs inject energy to or draw energy from the DN in a stochastic manner. A vehicle‐to‐grid service for voltage support of DN through controlled and coordinated EV charging and discharging techniques to maintain the DN voltage within the threshold limits is proposed. In this context, a fuzzy logic control (FLC) is developed to generate reference power signal and the power flow direction based on DN voltage and electric vehicle charging station's (EVCS) available energy. Here, the EVCS is a place where the EVs are charged and/or participate for grid support. Then, an EVCS aggregator is implemented to coordinate the large fleet of EVs based on FLC output and EV's available energy. Furthermore, an EV's battery charge and discharge rate controller is developed to control the EV's energy based on EVCS aggregator output and charge/discharge rate threshold limits. Finally, an active and reactive power control methodology is implemented to maintain DN voltage profile within the threshold limits. Extensive simulations are conducted based on real data from a radial distribution system. The results show that the EVCS can successfully maintain the DN voltage within the threshold limit through the proposed control and coordination strategy.